An embedded neutral layer for advanced surface affinity control in grapho-epitaxy directed self-assembly. Issue 23 (31st May 2018) - Delachat, Florian; Gharbi, Ahmed; Pimenta-Barros, Patricia; Fouquet, Antoine; Claveau, Guillaume; Posseme, Nicolas; Pain, Laurent; Nicolet, Célia; Navarro, Christophe; Cayrefourcq, Ian; Tiron, Raluca
Abstract : This work developed an innovative process for grapho-epitaxy DSA which enables independent control of the template surface affinities. Abstract : Advanced surface affinity control for grapho-epitaxy directed self-assembly (DSA) patterning is essential for providing reliable DSA-based solutions for the development of semiconductor patterning. Independent control of surface affinity between the bottom and the sidewalls of a topographical guiding structure was achieved by embedding an ultrathin layer in the guiding template stack. The implementation of an embedded layer with tunable surface properties for DSA grapho-epitaxy was evaluated and optimized on 300 mm wafers by critical dimension SEM characterization. It was demonstrated that a thin protective layer, placed between the hard mask guiding template and the embedded layer, allows the preservation of the surface properties of the embedded layer during guiding template etching. The DSA performances of this novel grapho-epitaxy integration, using a topographical template patterned with 193 nm immersion lithography, were evaluated by monitoring the success rate and the critical dimension uniformity of the shrunk contacts. FIB-STEM analyses were further carried out to analyze the residual polymer thickness on the resulting contacts. This new integration leads to the control of the polymer residual thickness (a few nanometers) and uniformity (inferior to 1 nm) at the bottom of the guiding template which will facilitate the subsequent DSA pattern transfer.